Home-schooling in the Republic of Ireland - Banks, Joanne (My University, 2023)
Internationally, there continues to be a rise in the popularity of home-schooling. Although the growth in the numbers of families choosing this alternative approach was evident prior to the Covid-19 Pandemic school closures, it appears to have impacted on the decision for some to home-school permanently. Using a scoping review of the literature, this paper considers the research evidence around home- schooling in the United Kingdom and Europe. It then focuses on home-schooling in the Republic of Ireland to assess the change and development of home-schooling over time. In line with trends internationally, Irish administrative data show an increase in the numbers of families engaging in home-schooling in recent years, particularly for students with disabilities. The paper situates these findings within the context of ongoing debates on inclusive and special education in Ireland and the capacity of mainstream schools to educate and include every student.
PUBLISHED
Keywords: Disability, exclusion, home education, home-school, implementation, inclusion, parents, Ireland; Inclusive Society; Alternative Modes Education; Education policy; Special Needs Education; Education